CRITICAL REVIEW IN INTEGRATING POINT-OF-CARE ULTRASOUND (POCUS) TRAINING INTO EMERGENCY NURSING EDUCATION PROGRAMS IN CURRENT PRACTICES AND FUTURE DIRECTIONS. - 1Hassan Ali Ali Almakayil, 2Mohammed Ali Ali Almakayil, 3Abdullah Ali Alialmakayeel, 4Mansour Mhdi Mohammed Al Slyeim, 5Hussain Ajaim Hussain Albahri, 6Mohammed Ajaim H Alnajrani, 7Mohamad Hassan Hamad Laslom, 8Mohammed Saleh Nasser Alyami, ,; 9Hamad Soeibsalehlaslom, 10Nasser Mohamed Ai Amer, 11Mahdi Salehnaseeralyami, 12Nasser Saleh Nasser Al-Yami, 13Abdullah Mana Abdullah Alrubua, (Chelonian Research Foundation, 2022)
Point-of-care ultrasound (POCUS) has become an imperative instrument to help make fast conclusions and decisions in critical care. It is critical to incorporate POCUS preparation in emergency nursing administrations so caregivers can utilize this device. This basic survey investigates current and future headings for the coordination of POCUS preparations into emergency medication programs. The writing survey recognizes the different strategies utilized in POCUS preparation, highlighting the benefits and challenges. Moreover, this survey discusses the significance of handle enhancement, educator preparation, and persistent execution assessment. There's a requirement for an approach combining recreation thinking with clinical education in POCUS preparation. The significance of intrigue collaboration and the integration of POCUS into the serious care program was emphasized within the dialog. In outline, proposals are advertised for routinely making strides in POCUS preparation, counting prepare change, instructor back, and noninvasive appraisal in emergency nursing education programs—future headings center on removing instruction innovation and extending the use of POCUS in basic care. Keywords: Point-of-care ultrasound, POCUS training, emergency nursing education, curriculum development, simulation-based learning.